Preoperative ICG fluorescence marking improves lymph node retrieval and survival in laparoscopic gastrectomy for gastric cancer - Yang, Weijun; Zheng, Wubin; Dong, Jianning; Shi, Xuesong; Nai, Yongjun (Frontiers in Oncology, 2025)
BackgroundWhile prior studies have suggested the potential benefits of preoperative indocyanine green (ICG) fluorescence marking in laparoscopic gastrectomy, few have evaluated its long-term oncologic impact in large real-world cohorts. This study aimed to validate the clinical utility of preoperative ICG marking by assessing its effects on lymph node retrieval and 3-year survival outcomes in gastric cancer patients.MethodsWe retrospectively analyzed resectable gastric cancer patients who underwent laparoscopic gastrectomy at Nanjing First Hospital between January 2020 and December 2021. Patients were allocated to an ICG or non-ICG group. In the ICG group, 1.25 mg/mL ICG was endoscopically injected around the tumor 12 to 24 hours prior to surgery, with near-infrared imaging guiding tumor resection and lymph node (LN) dissection. Propensity score matching yielded 168 matched pairs. Primary outcomes were LN yield and tumor localization accuracy; secondary outcomes included operation time, blood loss, and 3-year disease-free survival (DFS) and overall survival (OS). Multivariable Cox regression analysis was used to identify independent prognostic factors.ResultsThe ICG group demonstrated a significantly higher mean LN yield (46.4 ± 8.5 vs. 42.6 ± 11.5, P<0.01), lower noncompliance (31.0% vs. 49.4%, P<0.01), shorter operation time (200.0 ± 11.4 vs. 210.4 ± 11.6 minutes, P<0.01), and lower intraoperative blood loss (26.9 ± 8.7 vs. 31.3 ± 9.2 mL, P<0.01). The 3-year DFS and OS rates were significantly improved in the ICG group (DFS: 74% vs. 60%; OS: 80% vs. 66%; log-rank P<0.01). Multivariable Cox regression confirmed that ICG use was independently associated with improved DFS (HR=0.44, 95% CI: 0.28–0.71, P<0.01) and OS (HR=0.44, 95% CI: 0.25–0.76, P<0.01).ConclusionsPreoperative ICG fluorescence marking is a safe and effective adjunct in laparoscopic gastrectomy for gastric cancer, enhancing surgical efficiency and long-term outcomes.